(untitled) (American Journal of Food Science and Technology, 2023)
Non-dairy milk was produced from bioprocessed Bambara groundnut using submerged fermentation with bacterial strains of Lactobacillus plantarum [NRRL B-4306] and Lactobacillus fermentum [NRRL B-1932] obtained from the United States Department of Agriculture (USDA). Bambara groundnut was submerged in sterile water, inoculated with the starter culture containing 106 CFU/mL, and allowed to stand for 3 days. Bambara milk was produced by wet-milling the nut and the resulting paste cooked on medium heat for 20 min and strained with cheesecloth to remove the particles. Milk from non-inoculated Bambara nut and cow milk was used as positive and negative controls for sensory characteristics and nutritional comparison. The nutritional and sensory profile was compared to meet WHO recommended daily intake (RDA) with cow milk. Proximate composition of the samples ranged from 20.80 - 19.70, 57.20 - 52.25, 6.80 - 8.79% and 368.10 - 425.10 Kcal/100g for protein, carbohydrate, fat and energy, respectively. Results show that protein content of the fermented Bambara milk (19.70) was higher than cow milk (3.4) while fat content (8.79) was higher compared to cow milk (3.6 g/100g). Amino acids content ranged from 3.90 - 5.00, 9.00 - 14.20, 5.62 - 6.80, 0.6 – 0.92, 17.20 – 19.50, 3.35 – 3.80, 2.50 – 3.00, 3.80 – 4.15, 7.00 – 8.00, 2.90 – 4.50, 2.80 – 3.20, 4.80 – 5.10, 3.80 – 4.50, 2.60 – 3.80, 2.60 – 4.00, 3.50 – 3.90 and 4.10 – 4.85 for alanine, arginine, aspartic acid, cystine, glutamic acid, histidine, isoluecine, leucine, lysine, methionine, phenylalanine, proline, serine, threonine, tyrosine and valine, respectively. In-vitro protein digestibility increased from 70.74 - 89.70%, while anti-nutritional factors decreased from 4.72 – 2.08, 870.30 – 383.70, 1470.15 – 1023.10 and 1.85 – 0.55 mg/100g for tannin, polyphenol, phytate, oxalate and trypsin inhibition activity, respectively. Intensities of the sensory attributes was assessed based on parameters of appearance, aroma, mouth feel, consistency and overall acceptability using a nine-point Hedonic scale rating, and the results found to compare favorably with cow milk.